An algebra problem by Arpit Sah

Algebra Level 2

Solve for x , y and z : (x, y and z are positive)

xy + x + y = 23

yz + y + z = 31

zx + z + x = 47

What is x + y + z ?


The answer is 15.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

xy+x+y=23 ,so (x+1)(y+1)=24 similarly (y+1)(z+1)=32,(x+1)(z+1)=48

solving these eq. we get x=5,y=3,z=7

We may assume a=x+1, b=y+1, c=z+1 and solve easily to get a,b,c hence x,y,z.
But it is a briilliant solution.

Niranjan Khanderia - 7 years, 3 months ago
Tunk-Fey Ariawan
Mar 18, 2014

Rewrite x y + x + y = 23 x + ( 1 + x ) y = 23 ( 1 ) y z + y + z = 31 y + ( 1 + y ) z = 31 ( 2 ) z x + z + x = 47 x + ( 1 + x ) z = 47 ( 3 ) \begin{aligned} xy+x+y=23&\quad\quad\Rightarrow& x+(1+x)y=23&\quad(1)\\ yz+y+z=31&\quad\quad\Rightarrow& y+(1+y)z=31&\quad(2)\\ zx+z+x=47&\quad\quad\Rightarrow& x+(1+x)z=47&\quad(3) \end{aligned} First we eliminate z \,z by multiplying ( 2 ) (2) with ( 1 + x ) (1+x) and multiplying ( 3 ) (3) with ( 1 + y ) (1+y) and then subtracting, yield [ b ] r ( 1 + y ) x + ( 1 + y ) ( 1 + x ) z = 47 ( 1 + y ) ( 1 + x ) y + ( 1 + x ) ( 1 + y ) z = 31 ( 1 + x ) ( 1 + x ) y ( 1 + y ) x = 16 + 47 y 31 x \frac{ \begin{array}{c}[b]{r} (1+y)x+(1+y)(1+x)z=47(1+y)\\ (1+x)y+(1+x)(1+y)z=31(1+x) \end{array} }{ \quad\quad\quad\quad\quad\;\;(1+x)y-(1+y)x=16+47y-31x }- Hence ( 1 + x ) y ( 1 + y ) x = 16 + 47 y 31 x y + x y x x y 47 y + 31 x = 16 32 x 48 y = 16 2 x 3 y = 1 3 y = 2 x 1 y = 2 x 1 3 . \begin{aligned} (1+x)y-(1+y)x&=16+47y-31x\\ y+xy-x-xy-47y+31x&=16\\ 32x-48y&=16\\ 2x-3y&=1\\ 3y&=2x-1\\ y&=\frac{2x-1}{3}. \end{aligned} Substitute y \,y to ( 1 ) (1) , yield x + ( 1 + x ) ( 2 x 1 3 ) = 23 3 x + ( x + 1 ) ( 2 x 1 ) = 69 3 x + 2 x 2 + x 1 69 = 0 2 x 2 + 4 x 70 = 0 x 2 + 2 x 35 = 0 ( x + 7 ) ( x 5 ) = 0 x 1 = 7 or x 2 = 5. \begin{aligned} x+(1+x)\left(\frac{2x-1}{3}\right)&=23\\ 3x+(x+1)(2x-1)&=69\\ 3x+2x^2+x-1-69&=0\\ 2x^2+4x-70&=0\\ x^2+2x-35&=0\\ (x+7)(x-5)&=0\\ x_1=-7\quad&\text{or}\quad x_2=5. \end{aligned} Take the positive value of x \,x and find y \,y and z \,z . y = 2 x 1 3 y = 2 ( 5 ) 1 3 = 3 \begin{aligned} y&=\frac{2x-1}{3}\\ y&=\frac{2(5)-1}{3}\\ &=3 \end{aligned} and y + ( 1 + y ) z = 31 3 + ( 1 + 3 ) z = 31 3 + 4 z = 31 4 z = 28 z = 7. \begin{aligned} y+(1+y)z&=31\\ 3+(1+3)z&=31\\ 3+4z&=31\\ 4z&=28\\ z&=7. \end{aligned} Thus, x + y + z = 5 + 3 + 7 = 15 x+y+z=5+3+7=\boxed{15} .

how abt this xy(1/x + 1/y) + xy = 23 xy(1/x+1y+1) = 23 therefore xy = 23 or (1/x+1y+1) = 23 substituting xy = 23 in xy + y + x = 23 == 23 + (x + y) = 23 == x + y = 0 simlarly y +z and x + z = 0 therefore x + y +z = 0 u can substitute the value and u'll get the correct ans

Shubham Jain - 7 years, 2 months ago

You deserve level 5 Tunk Fey Ariawan

Saurav Sah - 7 years, 1 month ago
Sabarinath M S
Feb 28, 2014

we can use substitution method to solve this problem...

lets take 'x' as the subject & represent y,z in terms of x

♦(eqn.1) xy+ x +y = 23 ------> y = (23-x)/(1+x)

♦(eqn.3) zx+ z + x = 47 ------>z = (47-x)/(1+x)

substitute for y,z in (eqn.2) yz+y+z =31

===>{ (23-x)(47-x)/(1+x)² } + { (23-x)/(1+x) } + { (47-x)/(1+x) } = 31 ----- multiply both sides by (1+x)²

==>(23-x)(47-x) + ( (23-x )+(47-x) ) (1+x) = 31 (1+x)²

===> -32x²-64x +1120 =0

===>x²+2x -35 =0

-->(x+7)(x-5) = 0 ie x= 5 or -7

x>0(given) ====> x=5

y=(23-x)/(1+x)-----put x=5 ----> y=3

z=(47-x)/(1+x)-----put x=5-----> z=7

so (x,y,z) = (5,3,7) =====> x+y+z = 15

HENCE , (X+Y+Z =15 ) IS THE ANSWER

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...